Bonded logistics center and its impact on national automotive manufacturing industry - Achmad Riadi; Sunaryo (Jurnal Teknik Mesin Indonesia, 2023)
Pusat Logistik Berikat (PLB) or Bonded Logistics Center has been listed as a part of the Indonesia Economy Policy Volume II under the government of President Joko Widodo, as regulated in Government Regulation (PP) Number 85 Year 2015. PLB operations are expected to make national logistics activities more efficient, increase the availability of goods/raw materials needed by industries, increase local/foreign investment, and assist in the development of Indonesia as a logistics hub in the Asia Pacific region. The existence of PLB for automotive manufacturing industry is believed to have a special impact both in supporting the availability of automotive components and in increasing the competitiveness of exports of national automotive products. Especially with the regulation stipulated in Presidential Regulation Number 55 Year 2019, concerning the acceleration of the battery-based electric motor vehicle program. This paper aims to provide an analysis of the existence of PLB and its impact on national automotive manufacturing industry. The study was conducted by applying a dynamic system simulation to test the hypothesis of the PLB impact. Simulation model is a dynamic system approach using the Vensim®PLE8.0.4 program. The simulation results show the efficiency that can be obtained with the PLB. The ease of customs facilities obtained from PLB as well as the reduction in custom clearance time have a significant positive impact on the national automotive manufacturing industry.